PERHITUNGAN HARGA POKOK PRODUKSI PADA PT. WIJAYA MITRAMEGA PERKASA (METAL BED) SURABAYA - Yuli Vina Faatdin; Annisa Rahmawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
Cost of Production is the sacrifice of economic resources in processing raw materials into products. The purpose of this research is to describe the calculation of a reasonable cost of goods manufactured at PT. Wijaya Mitramega Perkasa (Metal Bed) Surabaya. The method used in this research is descriptive qualitative method. The results of this study indicate that the company has not implemented a reasonable cost of goods manufactured calculation. Therefore this study provides suggestions and reconstructs the calculation of a reasonable cost of goods manufactured, where all cost components in the calculation of the cost of goods manufactured are calculated in detail.